Multi-parameter coupling effects on plume morphology and pockmark development induced by submarine shallow gas leakage - Wang, Hao; Jiang, Jinnan; Ali, Muhammad; Liu, Xiaolei; Wang, Kan; Liu, Jiahao (Frontiers in Marine Science, 2025)
Plumes and pockmarks are formed when shallow gas breaches the seabed and infiltrates into ocean currents, disrupting the original ecological environment and affecting biological habitats and migration behaviors. An independently developed experimental system was employed in this study to investigate the effects of gas source pressure, burial depth, and number of release orifices on plume morphology and pockmark characteristics, aiming to evaluate their impacts on seabed ecological functions. Experimental results show that the maximum fountain height and plume diameter increase no-linearly with the increase in pressure and orifice number but decrease with increasing burial depth. The plume angle is positively correlated with pressure and negatively correlated with burial depth, showing no correlation with orifice number. Pockmark depth, diameter, and volume exhibit similar variation trends, with pressure being the dominant factor. Analysis of variance reveals that pockmark volume is most sensitive to pressure, while diameter has the least influence. Soil strength measurements after gas release demonstrate distinct patterns: strength increases in the pockmark center and external areas due to compaction, whereas it decreases in the waistline and edge regions due to shear failure. These changes may regulate benthic community distribution by altering sediment stability and pore water chemistry. The findings provide experimental insights into how gas release parameters influence submarine geomorphology and sedimentary environments, contributing to risk assessment of marine ecological disturbances associated with shallow gas activities.